2022
DOI: 10.1111/phpp.12841
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of light‐emitting diodes for skin therapy: Systematic review and meta‐analysis

Abstract: Light-emitting diodes (LEDs) are semiconductor devices that produce non-coherent, non-collimated, and narrow-spectrum lights (approximately 255-1300 nm) when a forward voltage is applied. 1,2 LED devices, including blue (420-440 nm), red (630-680 nm), and yellow (590-595 nm) LED lights, as well as near-infrared (LED-NIR; 750-1200 nm), are typically applied in five fields, including indicators and signs, lighting, data communication, machine vision systems, and especially, biological applications. 2 In fact, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…23 There is a large body of literature demonstrating the clinical benefits of photobiomodulation methods using lasers 24 or LED diodes. 25 However, PBM using light-emitting diodes has some advantages that should be considered when weighing the cost-effectiveness of these methods, particularly when used in public health systems where resources are generally scarce. PBM using LED therapy is, on average, much cheaper than laser devices.…”
Section: Discussionmentioning
confidence: 99%
“…23 There is a large body of literature demonstrating the clinical benefits of photobiomodulation methods using lasers 24 or LED diodes. 25 However, PBM using light-emitting diodes has some advantages that should be considered when weighing the cost-effectiveness of these methods, particularly when used in public health systems where resources are generally scarce. PBM using LED therapy is, on average, much cheaper than laser devices.…”
Section: Discussionmentioning
confidence: 99%
“…Blue-light PBM triggers a cascade of events attributable to the absorption of photons by intracellular photoreceptors. Among these effects, the impact of light on cytochrome-C oxidase can be observed: it induces an increase in cell proliferation, migration and differentiation, cytokine modulation, growth factor synthesis, and anti-inflammatory effects; thus, stimulating the improvement of the healing process [59,60].…”
Section: Blue Light Emission Diodementioning
confidence: 99%
“…Among them, LED yellow light, when absorbed by the skin, can treat telangiectasia, inhibit vascular neurogenic hyperreactivity, enhance skin tolerance and resistance, and reduce skin sensitivity. 11 Studies have shown that LED yellow light can inhibit the angiogenesis of human microvascular endothelial cells to improve erythema. 12 Based on this, LED yellow light may improve the itching, burning, stinging, and erythema symptoms of PPR.…”
Section: Introductionmentioning
confidence: 99%